Lekcja z historii kryzysów gospodarczych na świecie - Bochenek, Mirosław (Lesson in History of Economic Crises Around the World, 2009)
During the last 450 years over 70 global economic crises have been observed. First crises were caused by exogenous factors, the following, generated branches of economy, which became industrialized or acted as an impulse of economic boom and development preceding crisis. Although, they differed in appearance regularity, course, intensity, duration and extent of the damage, they proved to be inevitable. Despite pursuing a policy of stabilization, it was unable to exclude crises from economic life. Crises have been inseparable component of market economy.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 54-62